Efektifitas Usaha Zey Laundry di Jl. Caringin Pancoran Mas Depok - Irna Aryani (UM Purwokerto Press, 2023)
Entrepreneurial thinking is the initial capital and the basis for success at the same time. An entrepreneur mindset should be owned in running a business, including actively looking for new opportunities, daring to take risks, being actionoriented, never stopping learning, having a big vision, working in a team, loving business and focusing on market desires. Entrepreneurship is quite important to study, such as in terms of washing and washing affairs in daily life that so far not everyone is willing and able to wash clothes for various reasons and the effectiveness of the time used. Zey Laundry business is a kilo laundry business that takes advantage of this opportunity with its strategic business location. This study uses observations and interviews as well as a literature review of how the business can develop within three years, obstacles encountered during the business and additional prospects of customer loyalty can be used as business guarantees in the laundry business.